Potency of Various MicroRNA as Sputum Biomarker in Lung Cancer - Alnaz, Ahmad Razi Maulana; Abdillah, Aqyl Hanif; Ridha, Rasyid (Smart Medical Journal, 2022)
Introduction: Lung cancer is one the deadliest cancer known. Current method using low-dose CT scan to screen lung cancer applied are proved to reduce mortality, but lack in accuracy leading to overdiagnosis. Current researches are mostly seeking for a non-invasive and cost-effective method, hence biomarkers such as microRNA has a potency to screen and diagnose lung cancer. This literature review aimed to discuss the potency of microRNA in sputum as a biomarker in screening lung cancer.Methods: The study is conducted by literature searching for related journals in search engines such as PubMed, Science Direct, and Google Scholar with keywords. 35 articles were included with relevance and within 10 years publication.Result: MicroRNA is a short non-coding RNA which regulates gene expression. It acts in an oncogene or tumor suppressor gene regulation. DNA mutations or defects occurred in cancer particularly in lung cancer causes increase or decrease of microRNA expression. Alterations of microRNA expression in sputum detected by rt-PCR may represent progressions of lung cancer from a cell cycle dysregulation and provides better sensitivity and specificity among other biomarkers. Combinations of miRNA species offer increase of  sensitivity and specificity. Particular types of microRNA are able to classify the types of lung cancer in progress.Conclusion: MicroRNA has the promising potency and strong accuracy with a non-invasive and cost-effective procedure in detecting early signs of lung cancer occurrence and can be further applied as biomarker used in lung cancer.Keywords: Biomarker; Lung Cancer; microRNA; Screening; Sputum